The perspectives of pharmacy student preceptors on a service-learning program in primary health care: A qualitative study - Caroline Silva de Paula; Luciana Flavia de Almeida Romani; Marina Guimaraes Lima (Elsevier, 2023)
Background: There are a few studies about preceptorship in primary health care settings, but they didn't assess all possible contributions of this experience, such as preceptor behavioral changes and impact on health services. Objective: This study aimed to analyze the perspective of pharmacy student preceptors on a service-learning program carried out in a primary health care setting. Methods: This was a qualitative descriptive study, with semi-structured interviews and thematic analysis. The themes were defined deductively, according to levels of Kirkpatrick's theory about the impact of educational activities. Results: The preceptors showed positive and negative reactions to the structure of the service-learning program, developed their knowledge, changed behaviors such as collaborative interprofessional practice, and reported improvements in the health units. Conclusions: From the perspective of pharmacy student preceptor preceptors, the service-learning program had an impact on all levels expected for an educational activity according to Kirkpatrick's theory: reaction, learning, behavior, and results. These findings may inform the design of service-learning programs.